Bepridil opens the regulatory N-terminal lobe of cardiac troponin C - Li, Yu (The National Academy of Sciences, 2000)
Cardiac troponin C (cTnC) is the calcium-dependent switch for contraction in heart muscle and a potential target for drugs in the therapy of congestive heart failure. This calmodulin-like protein consists of two lobes connected by a central linker; each lobe contains two EF-hand domains. The regulatory N-terminal lobe of cTnC, unlike that of skeletal troponin C (sTnC), contains only one functional EF-hand and does not open fully upon the binding of Ca(2+). We have determined the crystal structure of cTnC, with three bound Ca(2+) ions, complexed with the calcium-sensitizer bepridil, to 2.15-Å resolution. In contrast to apo- and 3Ca(2+)-cTnC, the drug-bound complex displays a fully open N-terminal lobe similar to the N-terminal lobes of 4Ca(2+)-sTnC and cTnC bound to a C-terminal fragment of cardiac troponin I (residues 147–163). The closing of the lobe is sterically hindered by one of the three bound bepridils. Our results provide a structural basis for the Ca(2+)-sensitizing effect of bepridil and reveal the details of a distinctive two-stage mechanism for Ca(2+) regulation by troponin C in cardiac muscle.